2016
DOI: 10.2334/josnusd.15-0586
|View full text |Cite
|
Sign up to set email alerts
|

Association between periodontal status and idiopathic male infertility

Abstract: About 30% of male infertility cases are idiopathic. Previous studies reported a positive correlation between deep periodontal pockets and sperm sub-motility, which suggests that periodontitis might have a role in idiopathic semen abnormality pathospermia. We evaluated correlations between periodontal infection parameters and the results of sperm analysis of men with idiopathic infertility. In this observational study, semen quality and periodontal status were analyzed for 95 otherwise healthy men attending an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…Similarly to our previous study (Pasztor et al., ), significant correlation was found in a few analyses; for example, average number of teeth with calculus was higher in patients with combined oligo‐asthenozoospermia than with normospermia ( p = .048).…”
Section: Discussionsupporting
confidence: 88%
“…Similarly to our previous study (Pasztor et al., ), significant correlation was found in a few analyses; for example, average number of teeth with calculus was higher in patients with combined oligo‐asthenozoospermia than with normospermia ( p = .048).…”
Section: Discussionsupporting
confidence: 88%
“…A study by Pásztor et al. (2016) showed that poor periodontal conditions were not associated with any semen parameter abnormalities.…”
Section: Introductionmentioning
confidence: 95%
“…Both study protocols were approved by the Regional and Institutional Human Medical alcohol consumption and substance abuse) were collected via a self-administered questionnaire, followed by andrological and periodontal examinations [83,84].…”
Section: A Ethical Considerationsmentioning
confidence: 99%
“…The following exclusion criteria were defined: varicocele or testicular microlithiasis (confirmed by ultrasound examination); hypogonadism (verified by hormonal measurements); genetic disorders (determined by chromosome analysis or molecular genetic investigations) or symptoms of urogenital infection. Patients w ith azoospermia (no spermatozoa in the ejaculate) were also excluded due to the possibility of seminal duct obstruction or serious testicular abnormality [84].…”
Section: Adult Male Patientsmentioning
confidence: 99%
See 1 more Smart Citation